Głosuj na kandydatów FJN! - Miscewy, Mieczysław (1927-2015). ([S.l. : s.n.], 1969)
Plakat propagandowy z okresu wyborów w 1969 r.
Keywords: Wybory -- Polska -- 1945-1990 -- plakaty; Propaganda -- Polska -- 1945-1970 -- plakaty